Suburban Urbanities - Vaughan, Laura (UCL Press, 2015)
Suburban space has traditionally been understood as a formless remnant of physical city expansion, without a dynamic or logic of its own. Suburban Urbanities challenges this view by defining the suburb as a temporally evolving feature of urban growth. Anchored in the architectural research discipline of space syntax, this book offers a comprehensive understanding of urban change, touching on the history of the suburb as well as its current development challenges, with a particular focus on suburban centres. Studies of the high street as a centre for social, economic and cultural exchange provide evidence for its critical role in sustaining local centres over time. Contributors from the architecture, urban design, geography, history and anthropology disciplines examine cases spanning Europe and around the Mediterranean. By linking large-scale city mapping, urban design scale expositions of high street activity and local-scale ethnographies, the book underscores the need to consider suburban space on its own terms as a specific and complex field of social practice.